Assessment of impact of traffic-related air pollution on morbidity and mortality in Copenhagen Municipality and the health gain of reduced exposure. (December 2018) - Brønnum-Hansen, Henrik; Bender, Anne Mette; Andersen, Zorana Jovanovic; Sørensen, Jan; Bønløkke, Jakob Hjort; Boshuizen, Hendriek; Becker, Thomas; Diderichsen, Finn; Loft, Steffen
Abstract: Background: Health impact assessment (HIA) of exposure to air pollution is commonly based on city level (fine) particle concentration and may underestimate health consequences of changing local traffic. Exposure to traffic-related air pollution can be assessed at a high resolution by modelling levels of nitrogen dioxide (NO2 ), which together with ultrafine particles mainly originate from diesel-powered vehicles in urban areas. The purpose of this study was to estimate the health benefits of reduced exposure to vehicle emissions assessed as NO2 at the residence among the citizens of Copenhagen Municipality, Denmark. Methods: We utilized residential NO2 concentrations modelled by use of chemistry transport models to calculate contributions from emission sources to air pollution. The DYNAMO-HIA model was applied to the population of Copenhagen Municipality by using NO2 concentration estimates combined with demographic data and data from nationwide registers on incidence and prevalence of selected diseases, cause specific mortality, and total mortality of the population of Copenhagen. We used exposure-response functions linking NO2 concentration estimates at the residential address with the risk of diabetes, cardiovascular diseases, and respiratory diseases derived from a large Danish cohort study with the majority of subjects residing in Copenhagen between 1971 and 2010. Different scenarios were modelled to estimate the dynamic impact of NO2 exposure on related diseases and the potential health benefits of lowering the NO2 level in the Copenhagen Municipality. Results: The annual mean NO2 concentration was 19.6 μg/m 3 and for 70% of the population the range of exposure was between 15 and 21 μg/m 3 . If NO2 exposure was reduced to the annual mean rural level of 6 μg/m 3, life expectancy in 2040 would increase by one year. The greatest gain in disease-free life expectancy would be lifetime without ischemic heart disease (1.4 years), chronic obstructive pulmonary disease (1.5 years for men and 1.6 years for women), and asthma (1.3 years for men and 1.5 years for women). Lowering NO2 exposure by 20% would increase disease-free life expectancy for the different diseases by 0.3–0.5 years. Using gender specific relative risks affected the results. Conclusions: Reducing the NO2 exposure by controlling traffic-related air pollution reduces the occurrence of some of the most prevalent chronic diseases and increases life expectancy. Such health benefits can be quantified by DYNAMO-HIA in a high resolution exposure modelling. This paper demonstrates how traffic planners can assess health benefits from reduced levels of traffic-related air pollution. Highlights: Nitrogen oxide concentration can serve as a proxy of exposure to traffic-related air pollution. The annual mean nitrogen oxide concentration is 19.6 μg/m 3 in Copenhagen. One-year gain in life expectancy by lowering nitrogen oxide exposure to rural level Marked increase in disease-free life expectancies by reducing nitrogen oxide exposure